Early low‐dose rituximab for active thyroid eye disease: An effective and well‐tolerated treatment. (11th April 2019) - Insull, Elizabeth A.; Sipkova, Zuzana; David, Joel; Turner, Helen E.; Norris, Jonathan H.
Summary: Background: Thyroid eye disease (TED) is an autoimmune inflammatory disease that can be disfiguring and potentially sight threatening. Suppression of inflammation in active disease can reduce the risk of visual loss and limit long‐term sequelae. Current management involves inflammation suppression using glucocorticoids. The aim of this study was to evaluate the efficacy of early disease intervention with targeted immunomodulatory therapy to alter disease course. This paper reports the efficacy of low‐dose rituximab in reducing clinical activity in TED in a small population. Methods: A retrospective audit of consecutive patients with active TED managed primarily with a 100 mg rituximab infusion. Further glucocorticoid or steroid‐sparing agents were prescribed if clinically indicated. Clinical activity score, VISA overall severity score and Oxford Quality of Life score were recorded at each visit as well as TSH receptor antibody levels (TRAb), B cell subsets and adverse reactions. Results: Twelve patients had mean follow‐up of 6.3 months. Clinical activity scores significantly decreased (mean score 5.08 to 1.58; P  < 0.001), VISA overall severity scores reduced by 50% from 12 to 6, P  < 0.001 and the mean cumulative dose of IV methylprednisolone was 2.3 g. 100 mg rituximab induced significant CD19 + B cell depletion (n = 8, P  < 0.001). There was no significant reduction in serum TRAb (n = 8, P  = 0.06). A transient infusion‐related rash was the only adverse effect, n = 4. QoL scores did not differ markedly before and after treatment. Conclusion: Low‐dose rituximab is an efficacious, well‐tolerated and safe treatment for active TED; reducing disease activity and allowing reduced administration of systemic steroid.